Importance and Potential of European Cross-Border Deceased Donor Organ Allocation Through FOEDUS-EOEO Platform - Elmer, Andreas; Lütolf, Vera Valérie; Carella, Claudia; Beyeler, Franziska; Krügel, Nathalie; Straka, Libor; Cardillo, Massimo; Immer, Franz (Transplant international, 2023)
The FOEDUS-EOEO platform was relaunched in 2015 to allocate deceased donor organs across European borders when there are no suitable recipients in the donor's country. We analyzed organ offers from 01.06.2015-31.12.2021 and present the number of offers and transplants, and utilization as percentage of transplanted organs. 1,483 organs were offered, 287 were transplanted (19.4% utilization). Yearly number of offers and transplants increased from 2017 to 2021, while utilization stabilized after 2018. Utilization was highest for organs offered by Slovakia (47.2%), followed for organs offered by Lithuania, France, Greece, and Czechia (19.3%-22.9%). The most frequently offered organ was the heart (n = 405; 27.3%), followed by the lungs (n = 369; 24.9%) and the liver (n = 345; 23.3%). Utilization differed significantly by organ type (highest for liver, 35.7%; followed by heart, 18.8%; and kidney, 18.3%) and by donor age (highest for 1 to 5 year-old donors (25.0%)). FOEDUS-EOEO allowed for many European patients receiving a long-awaited transplant, especially for very young pediatric patients waiting for a liver, a heart, or a kidney. The increasing number of participating countries has increased both the number of offered organs and, to a lesser extent, the number of transplanted organs.
Keywords: získávání tkání a orgánů; transplantace ledvin; transplantace orgánů; Child, Preschool; Organ Transplantation; Infant; Kidney Transplantation; Humans; předškolní dítě; Tissue Donors; dárci tkání; Tissue and Organ Procurement; transplantáty; kojenec; dítě; lidé; Transplants; Child